Answer: 74 pounds
==============================================================
Step-by-step explanation:
For now, let's ignore the 73 pounds.
The 13 ounces she gains is added onto the initial 3 ounces to get 3+13 = 16 ounces = 1 pound.
So we add this 1 pound onto the 73 pounds from earlier to get the answer to be 73+1 = 74 pounds
-----------------
We could write the steps out like this
(73 pounds, 3 ounces) + (13 ounces)
(73 pounds + 3 ounces) + (0 pounds + 13 ounces)
(73 pounds + 0 pounds) + (3 ounces + 13 ounces)
73 pounds + 16 ounces
73 pounds + 1 pound
74 pounds